Biosolarization for the management of nematodes in a horticultural greenhouse in Costa Sacate, Córdoba, Argentina - Yosviak, Maria Iohanna; Meneguzzi, Natalia; Bono, C.; Arnedo, D. (2025)
Presentación en diapositivas y resumen